Desenvolvimento de scaffolds celulares vítreos a base de SiOC via digital light processing e avaliação de biocompatibilidade in vitro - Carnieri, Matheus Versão (2023)
The main objective of the present study was the creation and characterization of silicon-based glassy cellular scaffolds (SiOC) using the Additive Manufacturing (AM) technique of Digital Light Processing. Scaffolds are complex and ordered structures that can directly influence the biological and mechanical characteristics of the produced parts. Throughout the project, several crucial factors were investigated to control the morphology and strength of the scaffolds, including the thermal debinding cycle, the rheology of the raw material, geometric modeling of ordered pores, and manufacturing and post-processing parameters. Among the results obtained, it is worth highlighting that the produced scaffolds exhibited a linear shrinkage of approximately 50% and a mass variation of 71.8 ± 1.9%. They also had a 72.69 ± 0.04% porosity and a macropore size of 741.6 ± 39.6 µm. Regarding the structure of the parts, they showed stable and uniform retraction structures, with three-point bending tests providing an average strength of 7.8 ± 1.0 MPa. These values are close to the flexural strengths of spongy bones and feature geometric pore characteristics favorable to cell growth and proliferation. Plasma treatment significantly improved the hydrophilicity of the parts, with the potential for a positive impact on the biological applications of the scaffolds. Regarding biological assays, direct contact tests with hASCs cells confirmed that the produced scaffolds are not cytotoxic. Subsequently, fluorescence microscopy and scanning electron microscopy (SEM) allowed for the evaluation of cell adhesion and proliferation behaviors. Over 14 days of cultivation, there was intense cell proliferation, with cellular cytoskeletons growing, “interweaving,” and distributing themselves, indicating a positive interaction between cells and sample surfaces. Finally, it was observed that hASCs cells cultivated on the scaffolds exhibited desirable characteristics for osteogenic differentiation. These results suggest that the SiOC scaffolds produced provide biocompatible environments conducive to osteogenic differentiation and bone regeneration.